Pelatihan Pembuatan Otomatisasi Berbasis Arduino di MA Al Madinah Nogosari Boyolali - Suharno; Harjunowibowo, D; Rezeki, YA; Budiawanti, S; Raharjo, DT; Jamaludin, A; Rahmasari, L (Bahasa Indonesia, 2025)
Currently, the development of the internet of things has contributed to the progress of industrial technology and one of them is the development of sensor technology through automation technology. The advancement of sensor technology has changed the pattern of human life towards digitalization. Sensor technology needs to be developed among young people, especially students, through knowledge of simple sensor technology so that students are interested and able to continue to develop their knowledge. Community service activities at MA Al Madinah aim for students to understand and be able to apply simple sensor technology based on Arduino. Simple automation training with Arduino is a community service activity at MA Al Madinah which is attended by students and as a form of stages of implementing module development. Module development through stages of needs analysis, design, development, implementation, and evaluation which aim to ensure that the module is suitable for use for training. The results of expert validation of the developed module obtained a very good category, the results of student assessments through limited training obtained very suitable for use, and the results of the training evaluation were very good, which is expected to be continued with more participants at MA Al Madinah Nogosari Boyolali   Abstrak Saat ini perkembangan internet of things telah memberikan kontribusi pada kemajuan teknologi industri dan salah satunya perkembangan teknologi sensor melalui teknologi otomatisasi. Kemajuan teknologi sensor telah mengubah pola kehidupan manusia menuju digitalisasi. Teknologi sensor perlu ditumbuhkan kepada kalangan muda terutama para pelajar melalui pengetahuan teknologi sensor sederhana agar para pelajar tertarik dan mampu mengembangkan terus pengetahuannya. Kegiatan pengabdian di MA Al Madinah bertujuan peserta didik memahami dan mampu menerapkan tentang teknologi sensor sedehana berbasis Arduino. Pelatihan otomatisasi sederhana dengan Arduino merupakan kegiatan pengabdian di MA Al Madinah yang diikuti peserta didik dan sebagai bentuk tahapan penerapan pengembangan modul. Pengembangan modul melalui tahapan analisis kebutuhan, perancangan, pengembangan, implementasi, dan evaluasi yang bertujuan untuk memastikan modul layak digunakan untuk pelatihan. Hasil validasi ahli terhadap modul yang dikembangkan diperoleh kategori sangat baik, hasil penilaian peserta didik melalui pelatihan terbatas diperoleh sangat layak digunakan, dan hasil evaluasi pelatihan diperoleh sangat baik yang  diharapkan diteruskan dengan peserta lebih banyak lagi di MA Al Madinah Nogosari Boyolali.